Value Orientation and Ecoliteracy as Key Factors in Green Product Purchase Decisions - Rahmaningtyas, Avivah; Cahyaningtyas, Nur Indah; Putri, Levana Masitajasmin; Fadhilah, Muhammad Luthfie; Novitaningrum, Restie; Fauziah, Irma; Simamora, Liska (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Consumer awareness regarding health and environmental sustainability has increased interest in green products. Companies now recognize the importance of understanding consumer behavior in purchasing eco-friendly products, as trust and perceptions of safety significantly influence market success. This study aims to analyze how consumer ecoliteracy and value orientation affect purchasing decisions for Chocolate Monggo’s green products, providing insights to support effective marketing strategies for sustainable food brands. This study was conducted using ecoliteracy and value orientation as independent variables and purchase decision as the dependent variable. Data were collected via a Google Form and analyzed through Structural Equation Modelling (SEM) using Partial Least Squares (PLS) in SmartPLS 4.0. The findings reveal that ecoliteracy and value orientation are significant to consumers’ purchasing decisions for Chocolate Monggo. These results suggest that Chocolate Monggo should focus on strategies to elevate public ecoliteracy and promote the personal and social benefits associated with green product consumption.